(untitled) (FULafia Journal of Science and Technology, 2024)
An investigation into the corrosion inhibition potentials of the flower of Cucurbita pepo was undertaken. The gravimetric and gasometric methods of corrosion measurements were employed at temperatures of thirty and sixty degree celcius. Ethanoic extract of the flower of Cucurbita pepo was used as a corrosion inhibitor in 0.5 M HCl and the results revealed that it mitigated the corrosion of mild steel in the acidic medium. The inhibition efficiency of the plant increased with concentration and it is temperature dependent. The experimental data fitted to the Temkin adsorption isotherm model. A mechanism of physical adsorption is proposed for the corrosion inhibition process. This work provides novel information on the possibility of using the flower of Cucurbita pepo as a corrosion inhibitor.